2014
DOI: 10.1097/01.npr.0000452978.99676.2b
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based diagnosis and management of acute bronchitis

Abstract: Acute bronchitis is a common respiratory infection seen in primary care settings. This article examines the current evidence for diagnosis and management of acute bronchitis in adults and provides recommendations for primary care clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
0
1
0
1
Order By: Relevance
“…Продолжаю щийся воспалительный процесс усиливает отечность эпителия, угнетает мукоцилиарный клиренс в дыхательных путях. В связи в этим происходит патологическое нарушение нервной и гуморальной регуляции в слизистой оболочке дыхательных путей, что приводит к изменению вязкости бронхиального секрета и снижению в нем концентрации лизоцима, белка и сульфатов [32,33].…”
Section: рациональная фармакотерапияunclassified
“…Продолжаю щийся воспалительный процесс усиливает отечность эпителия, угнетает мукоцилиарный клиренс в дыхательных путях. В связи в этим происходит патологическое нарушение нервной и гуморальной регуляции в слизистой оболочке дыхательных путей, что приводит к изменению вязкости бронхиального секрета и снижению в нем концентрации лизоцима, белка и сульфатов [32,33].…”
Section: рациональная фармакотерапияunclassified
“…The symptoms include cough and expectoration caused by inflammation of the bronchial mucosa. The disease commonly occurs in infants and its morbidity is higher in the winter and spring (1,2). Modern medical research has demonstrated that the disease is mainly caused by viruses, bacteria or mixed infection (3).…”
Section: Introductionmentioning
confidence: 99%